The Establishment of a Discrete Element Model of Wheat Grains with Different Moisture Contents: A Research Study - He Li; Guangmeng Guo; Lu Xun; Junhao Lu; Huanhuan Chen; Gongpei Cui (Agriculture)
The high moisture content of wheat grains in extreme weather, such as continuous rain, can easily cause mildew, and we lack accurate discrete element parameters when conducting a simulation analysis of the rapid dehumidification of high-moisture grains. Based on the material characteristics of wheat grains with a moisture content ranging from 10.41% to 32.51%, the key parameters of discrete element simulation were calibrated. Firstly, the stacking angle under different moisture contents was determined by a physical experiment, and the regression equation was established as R2 = 0.9981. Subsequently, three significant parameters, namely, the static friction coefficient between the grains and steel plates, the static friction coefficient between grains, and the rolling friction coefficient, were selected from nine parameters using the Plackett–Burman test and the steepest climbing test. Furthermore, the stacking angle–discrete element parameter model was established using the Box–Behnken test as R2 = 0.98, with a relative error of less than or equal to 3.28%. Finally, the moisture content–discrete element parameter model was derived and constructed based on the moisture content–stacking angle model and the stacking angle–discrete element parameter model, with a relative error of less than or equal to 3.92%. The results indicate that the discrete element simulation parameters of wheat grains can be directly predicted by the moisture content and used for the discrete element simulation testing of high-moisture wheat grains. This universal calibration method not only provides convenient and reliable technical support for optimizing the emergency rapid dehumidification process for high-moisture wheat grains but also provides a reference method for the calibration of other grains.